Efficacy and safety of once-weekly semaglutide monotherapy in a young subject with Prader-Willi syndrome, obesity, and type 2 diabetes: a case report - Dinoi, Elisa; Daniele, Giuseppe; Michelucci, Angela; Baldinotti, Fulvia; Campi, Fabrizio; Marchetti, Piero; Del Prato, Stefano; Dardano, Angela (Frontiers in Endocrinology, 2025)
BackgroundThe treatment of obesity and type 2 diabetes (T2D) in Prader-Willi syndrome (PWS) is still a challenge. Glucagon-like peptide 1 receptor agonists (GLP-1 RA) are attractive options, since they effectively reduce weight and improve blood glucose, without increasing the risk of hypoglycemia. However, data on their use in PWS are scarce.Case descriptionIn 2019, a 27-year-old male came to our Clinic because of first appearance of severe hyperglycemia (fasting plasma glucose 22.5 mmol/L). Based on clinical presentation, PWS was suspected, and diagnosis was confirmed by genetic tests. The patient was discharged on a basal-bolus insulin therapy managed by his parents due to his cognitive impairment. In spite of COVID-19 pandemic, the patient achieved tight glycemic control (HbA1c 41 mmol/mol) with non-severe hypoglycemic events in the face of significant body weight (BW) increase (+ 13 kg vs baseline). Insulin therapy was then discontinued, and once-weekly semaglutide (up to 0,5 mg weekly) was started. At 12-month follow-up, BW dropped from 79 to 73 kg while maintaining excellent glycemic control (HbA1c 40 mmol/mol). At 24-month follow-up, glycemic control remained optimal (HbA1c 38 mmol/mol) with further BW reduction (71 kg). Neither hypoglycemia nor gastro-intestinal or psychiatric adverse events were reported.ConclusionThis case supports the potential use of semaglutide for the treatment of subjects with PWS, obesity and T2D. Ad hoc trials are needed to evaluate the long-term efficacy and tolerability in these subjects.